VIETNAM DAN INDONESIA DI AWAL PANDEMI COVID-19 - Rizky Octa Putri Charin; Fadli Afriandi (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
Abstract This paper is a comparative study between Vietnam and Indonesia in handling COVID-19. The comparison between the two countries is viewed from the political approach of the government. The aim is to find out how to handle the crisis in two countries that have different political and governmental systems. The main finding of this study is that countries with communist (centralized) forms of government have better command and coordination, compared to democratic (decentralized) countries when facing a crisis, in this case study COVID-19. This paper is a qualitative research with data collection techniques is literature study. There are differences in responses that have an impact on handling in Indonesia and Vietnam. This difference in handling is related to the centralized system of communism or one command that makes clear and firm instructions in dealing with COVID-19 so that victims can be minimized. In contrast to Vietnam, Indonesia as a decentralized democracy has a slow pace and different policies between the center and the regions. This condition causes confusion in coordination so that people experience misinformation in their understanding of COVID-19, which then has an impact on increasing the number of positive cases of COVID-19.